Spinal Anaesthesia Vs General Anaesthesia for Open Cholecystectomy Operation Interim Analysis of a Controlled Randomized Trial - Zahid, M Abu (TAJ: Journal of Teachers Association, 2011)
This is a prospective randomized clinical study was done in different clinics in Rajshahi city from September 2011 to September, 2012 to evaluate the outcome of patient undergoing cholecystectomy operation by spinal Anaesthesia. This is also a comparative study of patient undergoing cholecystectomy operation either by spinal Anaesthesia or by general Anaesthesia. For this study 100 patient of open cholecystectomy were randomly selected in to two groups (Each group contain 50 patients). Group A patient received spinal Anaesthesia with some sorts of IV anaesthetic drugs such as low dose ketamine with atropine or low dose Opioids if necessary before surgical incision. Group B patients received general Anaesthesia as usual procedure. Then these patient were monitored during per-operative and postoperative period to evaluate its outcome. After completion of the operation we seen that those patient received spinal Anaesthesia had better outcome then general Anaesthesia undergoing open cholecystectomy operation. TAJ 2011; 24(1): 30-33